Asymmetric competition for nectar between a large nectar thief and a small pollinator: an energetic point of view - Padyšáková, Eliška; Okrouhlík, Jan; Brown, Mark; Bartoš, Michael; Janeček, Štěpán (Oecologia, 2017)
There are two alternative hypotheses related to body size and competition for restricted food sources. The first one supposes that larger animals are superior competitors because of their increased feeding abilities, whereas the second one assumes superiority of smaller animals because of their lower food requirements. We examined the relationship between two unrelated species of different size, drinking technique, energy requirements and roles in plant pollination system, to reveal the features of their competitive interaction and mechanisms enabling their co-existence while utilising the same nectar source. We observed diurnal feeding behaviour of the main pollinator, the carpenter bee Xylocopa caffra and a nectar thief, the northern double-collared sunbird Cinnyris reichenowi on 19 clumps of Hypoestes aristata (Acanthaceae) in Bamenda Highlands, Cameroon. For comparative purpose, we established a simplistic model of daily energy expenditure and daily energy intake by both visitor species assuming that they spend all available daytime feeding on H. aristata. We revealed the energetic gain-expenditure balance of the studied visitor species in relation to diurnal changes in nectar quality and quantity. In general, smaller energy requirements and related ability to utilise smaller resources made the main pollinator X. caffra competitively superior to the larger nectar thief C. reichenowi. Nevertheless, sunbirds are endowed with several mechanisms to reduce asymmetry in exploitative competition, such as the use of nectar resources in times of the day when rivals are inactive, aggressive attacks on carpenter bees while defending the nectar plants, and higher speed of nectar consumption.
Keywords: Feeding Behavior; Passeriformes; opylení; Pollination; Sunbird; Flowers; Bees; sociální chování; Plant Nectar; květy; Cinnyris; Africa; Animals; Carpenter bee; stravovací zvyklosti; Social Behavior; zvířata; včely; Hypoestes; Xylocopa; rostlinný nektar